Knowledge of needle sticks injuries and its prevention among interns and post graduate students working at a tertiary health care centre, Bangalore - Vijay, Christy; Joe, Allen; Ramesh, Naveen (International Journal Of Community Medicine And Public Health, 2017)
Background: Health care workers (HCW) especially doctors and nurses are at an increased risk of accidental needle stick injuries (NSI) due to the occupational environment in which they work. Hence the HCWs are at a higher risk of acquiring blood borne pathogens such as HIV, hepatitis B and C and other diseases. This study was done to assess knowledge regarding NSI and practice regarding disposal of needles and sharps among interns and postgraduate students. Methods: This study was a cross-sectional study done among 110 interns and postgraduates medical students working in various departments of a tertiary health care centre in Bangalore. A self-administered questionnaire was used to collect the data regarding knowledge, practices and preventive measures among HCWs in their work place. Results: Among the 110, 55 (50%) were from intern category and 55 (50%) were from the postgraduate category and 47 (42.7%) were male and 63 (57.3%) were female students. The prevalence of NSI was found to be 36.3%. Female participants and post graduates had better knowledge. Female participants and interns had better practice. Conclusions: The Knowledge among the medical students (interns and postgraduates) was inadequate, indicating the need for awareness programs to reduce the burden of NSI among HCWs.